Restriction Analysis of β‐Tubulin Gene for Differentiation of the Common Pathogenic Dermatophytes. Issue 2 (6th January 2014) - Abastabar, Mahdi; Mirhendi, Hossein; Rezaei‐Matehkolaei, Ali; Shidfar, Mohammad Reza; Kordbacheh, Parivash; Makimura, Koichi
<x xml:space="preserve">Abstract</x> Background Identification of dermatophytes at the species level, relying on macro‐ and microscopic properties of the colonies is time‐consuming, questioned in many circumstances, and requires considerable expertise. In this study, we examined the potency of a new genetic marker, β‐tubulin (BT2) gene, for differentiation of dermatophytes in an in silico and experimental restriction fragment length polymorphism (RFLP) profile. Methods The BT2 sequences of dermatophyte species were retrieved from GenBank and analyzed using bioinformatics softwares to choose suitable restriction enzyme(s). Forty reference culture collections and 100 clinical isolates were PCR‐amplified using the primers T1 and Bt2b and consequently subjected to virtual RFLP analysis. The dermatophytes were identified according to specific lengths of bands in agarose gel electrophoresis. Results After digestion of partially amplified β‐tubulin gene with the restriction enzyme FatI, three dermatophyte species, that is, Microsporum gypseum, M. canis, and Trichophyton verrucosum yielded unique restriction maps while the remaining species including T. interdigitale, T. rubrum, T. tonsurans, T. schoenleinii, and T. violaceum, were identified by further restriction digestion by Alw21I, MwoI, and HpyCH4V endonucleases. The length of RFLP products was same as of those expected by computer analysis. Conclusion The two‐step BT2 restriction mapping used in this study is an effective tool for reliable differentiation of the clinically relevant species of dermatophytes.